2008
DOI: 10.1111/j.1558-5646.2008.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Spread of Neutral Alleles in the Cytonuclear System

Abstract: Neutral alleles can eventually pass a hybrid zone and their initial clines generated by a pure diffusion process dissipate with time, irrespective of the presence or absence of physical barriers. However, the transient neutral clines at the nuclear or organelle sites can be reinforced by the cytonuclear disequilibrium generated by diploid seed and haploid pollen dispersal. In this study, the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 64 publications
1
21
0
1
Order By: Relevance
“…Locus B is subject to the balance among the effects of immigration, genetic drift, and recombination with locus A . This consideration is similar to the previous studies in examining associative overdominance or genetic hitchhiking effects on spreading neutral nuclear/organelle genes [44], [53], [54], [55]. All items with, , and are eliminated for the average per-generation changes in allelic frequency, gametic and zygotic LDs in the formulae in Appendix S2.…”
Section: Resultsmentioning
confidence: 84%
“…Locus B is subject to the balance among the effects of immigration, genetic drift, and recombination with locus A . This consideration is similar to the previous studies in examining associative overdominance or genetic hitchhiking effects on spreading neutral nuclear/organelle genes [44], [53], [54], [55]. All items with, , and are eliminated for the average per-generation changes in allelic frequency, gametic and zygotic LDs in the formulae in Appendix S2.…”
Section: Resultsmentioning
confidence: 84%
“…Without loss of comparing zygotic and composite digenic LDs, we consider the coincident clines between two loci, which enhances reproductive isolation and genomic cohesion [35], [45]. Let s 1  =  s 2  =  s , h 1  =  h 2  =  h , g 1  =  g 2  =  g , p A  =  p B  =  p , and q  = 1- p for a population at position x .…”
Section: Resultsmentioning
confidence: 99%
“…It is well understood that natural hybrid zones provide an excellent natural laboratory to study the mechanisms of postzygotic isolation [45], [48], [49]. Barriers to gene introgression are expected to be greater for the genes associated with reproduction isolation than for the neutral genes [49], [50].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Hu (2008) showed that CND should limit the separation of neutral and selected clines, and so the extent to which these genomes are linked makes the pattern observed so far an unusual one. However, Hu (2008) also notes that selective clines often will act as asymmetric barriers to the spread of neutral alleles, a common result for introgression (Arnold 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Hu (2008) showed that CND should limit the separation of neutral and selected clines, and so the extent to which these genomes are linked makes the pattern observed so far an unusual one. However, Hu (2008) also notes that selective clines often will act as asymmetric barriers to the spread of neutral alleles, a common result for introgression (Arnold 2006). Overall, this finding suggests that more information about Notochthamalus will be recovered from further exploration in locations to the south of Niebla; additional genotyping also will be necessary to increase the power of this test, as the five loci indicated have only marginally significant results for the CND test; correction for multiple testing would, in fact, require a P -value of <0.003, which none of these loci obtain.…”
Section: Discussionmentioning
confidence: 99%